Pharmacotherapy for Comorbid Adult Attention-Deficit Hyperactivity Disorder and Stimulant Dependence: A Systematic Review - LS, Woon; Z, Hazli; LLY, Gan (IIUM Medical Journal Malaysia, 2020)
Comorbid adult attention-deficit hyperactivity disorder (ADHD) and stimulant dependence is widely recognized, but efficacy of pharmacotherapy in this patient population is not well established. We aimed to review whether pharmacotherapy is efficacious in reducing ADHD symptoms and stimulant use in comorbid adult ADHD and stimulant use disorder. English articles until June 2017 were systematically searched in electronic databases (MEDLINE and PsycINFO), an online clinical trials register (ClinicalTrial.gov), and through hand-search of article references. Randomized, double-blind, placebo-controlled trials that studied efficacy of pharmacotherapy in adults with comorbid ADHD and stimulant dependence were included. Two reviewers assessed studies for inclusion and extracted data; disagreements were resolved by consensus. Study outcomes included were changes in ADHD symptom severity, substance abstinence, treatment retention rates and safety. From the 1394 records identified, five trials (n=358) were included. Four studies involved methylphenidate; in another study extended-release mixed amphetamine were used. The comorbid stimulant was cocaine in three studies, and amphetamines in the rest. All were short-term studies involving predominantly young male adults conducted in outpatient settings. There is early promising but mixed evidence for therapeutic efficacy in improving ADHD symptoms. Stimulant medications did not worsen stimulant dependence or adverse effects of stimulant medications. Side effects were mild and tolerable. High attrition rates and small sample size limited the generalizability of findings. Current limited evidence suggests that stimulant treatment for comorbid adult ADHD and stimulant dependence is feasible. Welldesigned trials with adequate power are needed for more robust evidence on ADHD and stimulant use outcomes.